2018
DOI: 10.1021/acssuschemeng.8b06184
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Value-Added Products and Thermochemical Synthesis of Platform Chemicals from Food Waste

Abstract: Immense global generation of food waste calls for advanced technologies to maximize the use of such renewable carbon-based resources. In this study, corn, taro, lettuce, and bean sprout, were valorized for the production of value-added chemicals via sequential supercritical CO2 (scCO2) extraction and thermochemical conversion. The scCO2 extraction was performed at 350 bar and 50 °C for 60 min. The extracts of the lettuce contained sterols (764 μg g–1) that have potential anticancer properties. While bean sprou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Integrated biorefinery, i.e., implementing various conversion approaches in tandem or in series, is drawing more attention from scholars in recent studies [215]. In this way, valorization of food wastes forms a circular bio-economy with more efficient recovery of each reusable stream (e.g., higher carbon efficiency) to obtain diverse range of products, such as biofuels, platform chemicals, and advanced biomaterials.…”
Section: Perspectives For Future Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrated biorefinery, i.e., implementing various conversion approaches in tandem or in series, is drawing more attention from scholars in recent studies [215]. In this way, valorization of food wastes forms a circular bio-economy with more efficient recovery of each reusable stream (e.g., higher carbon efficiency) to obtain diverse range of products, such as biofuels, platform chemicals, and advanced biomaterials.…”
Section: Perspectives For Future Developmentmentioning
confidence: 99%
“…For instance, a syrup containing 89 g/L fructose was produced from enzymatic saccharification and isomerization of food and beverage waste, which was then subjected to catalytic reaction and produced 71 mol% HMF at 140 °C within 40 min using Amberlyst 36 catalyst [168]. Another recent study proposed the supercritical CO 2 extraction of high-value products (e.g., esters, fatty acids) from vegetables, from which the solid residues were utilized as feedstock for HMF synthesis [215]. Another possibility is to combine waste-to-energy technologies, which are commercially mature in market, with emerging biorefineries.…”
Section: Perspectives For Future Developmentmentioning
confidence: 99%
“…SnCl 4 was surely the preferred salt for HMF synthesis from raw biomasses, and other researchers have tested it as a catalyst. For example, Yu et al investigated HMF synthesis in the presence of SnCl 4 under MW heating, starting from different food wastes, such as bread waste [103,[107][108][109], unskinned kiwi fruit [104], watermelon flesh [104], rice waste [104,106], corn waste [110], and taro waste [110]. Performing the reaction under the same conditions (140 • C and 20 min) in the solvent system H 2 O/DMSO (1/1 v/v), the authors reported different HMF yields depending on the starting biomass (runs 77-81, Table 4) [103,104].…”
Section: Biphasic And/or Multiple-solvent Systemsmentioning
confidence: 99%
“…Although FLW minimization is crucial in feeding more people and in reducing the environmental impacts of the food chain, there are unavoidable losses resulting from food production and processing. Hence, FLW valorization is a complementary approach that allows the recovery or upcycling of resources for a variety of purposes, including those associated with energy, [ 15,16 ] animal feed, chemicals, [ 17 ] and materials. [ 18 ] Since the transformations needed for FLW valorization, on their own, might involve additional environmental impacts, one needs to consider the feasibility of each valorization initiative in a holistic manner, for example, by using life cycle assessments (LCA) and other approaches to support decision‐making.…”
Section: Losses and Waste Associated With The Food Industry And Oppor...mentioning
confidence: 99%